A new species of Sumampattus Galiano, 1983 from Brazil (Araneae: Salticidae: Freyina). (2nd January 2023) - Marta, Kimberly S.; Figueiredo, Cassiano P.; Rodrigues, Everton Nei Lopes
ABSTRACT: Sumampattus Galiano, 1983 comprise three species from South America, the genus is diagnosed by the male palps with an embolus and a cymbial groove with an inclination to the prolateral side, accompanied by a membranous conductor and proximal retrolateral lobe of tegulum distal division, emerging from the dorsal border, moderately turned and twisted. In females, the epigynum has a large posterior atrium, accompanied by a carena septum and absent visible posteriorly-opening coupling pocket. In this work, a new spider species Sumampattus verae sp. n. (male and female) found associated with low vegetation in the Pampa Biome, Southern Brazil, is diagnosed, illustrated and described. Notes on polymorphism in color identified in the new species is herein described. All specimens were collected by D-vac in a grassland habitat. http://www.zoobank.org/urn:lsid:zoobank.org:act:40D51639-9F66-4461-973F-10586D922D31